CLINIC CHARACTERISTICS OF CHRONIC HEPATITIS C WITH STEATOSIS - Shamsiyeva Muattar Axmatovna (Web of Journals Publishing, 2025)
Chronic Hepatitis C (CHC) is a major global health issue, with a substantial number of affected individuals developing hepatic steatosis. This study aims to analyze the clinical characteristics of CHC patients with hepatic steatosis, elucidating its impact on disease progression, liver function, and treatment response. Understanding these characteristics is crucial for optimizing therapeutic strategies and improving patient outcomes.
Keywords: Chronic Hepatitis C, hepatic steatosis, fibrosis, metabolic syndrome, antiviral therapy, hepatocellular carcinoma, genetic predisposition.